Pengaruh Model Pembelajaran QODE (Questioning, Organizing, Doing, Evaluating) Materi Sistem Ekskresi terhadap Hasil Belajar Peserta Didik - Tang Silmy Zahrah; Mashuri Masri; Syahriani, Syahriani (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
The aims of this study were to find out the learning outcomes of students who were taught using the QODE learning model (Questioning, Organizing, Doing, Evaluating), to find out the learning outcomes of students who were taught without using the QODE learning model, and to know the effect of the QODE learning model on student learning outcomes. Quasi-experiment is a type of research that is applied to the nonequivalent control group design as the design in this study. The population of this study was 65 students from class XI IPA SMA Negeri 9 Pangkep. Class XI IPA 1 with 22 students was used as the control class and class XI IPA 2 with a total of 22 students was used as an experimental class using purposive side as a sampling technique. The research instrument used was a learning achievement test that aimed to measure student learning outcomes in the number of 25 multiple choice questions. Descriptive analysis as well as inferential analysis were used in the research. The results of the study showed that the average score of students' learning outcomes was 82.91 in the experimental class and 71.27 in the control class. The results of the t test show a sig.(2-tailed) value of 0.000 < α = 0.05. This shows that Ha is accepted, meaning that there is a significant difference between the learning outcomes of students who are taught using the QODE learning model and students who do not use the QODE learning model.